Respon Al-Qur’an terhadap Tantangan Artificial Intellegence (AI) dan Relevansinya dengan Indonesia Emas 2045 - Masruri, Hamdan Al; Chusbyah, Nila; Ma'arif, Cholid; Dewi, Mariska Nirmala (Canonia Religia, 2025)
In this paper, the author reveals the challenges of AI and its solutions based on the verses of the Qur'an in a descriptive-analytical manner. To build a solid theological-practical framework for the development of science and society. This qualitative research uses a literature review and approaches a thematic interpretation of the concept of artificial intelligence. The material object of this research is several related verses of the Qur'an, while the formal object is thematic AI challenges and their solutions. The results of this study show that five Qur'aniy solutions can at least answer AI challenges. Among them are: a) QS. al-Mujadilah:11 is about the claim of mastery of AI technology; b) QS. al-'Arāf: 31 relates to the use of AI not excessively; (c) QS. al Hujurat: 6 about the ethics of filtering before sharing knowledge; d) QS. Saba': 11 alludes to the limits of religion that cannot be violated in the mastery of AI; e) QS. al-Ra'd: 11 questions the guarantee of the critical position of humans in the onslaught of AI technology. From these five points, it can be concluded that the main challenge in developing AI technology is the readiness of human resources. Both users, creators, and providers must have a strong commitment to science, good morals in controlling technology, and a firm belief that humans as servants of God still play a greater role than technology itself. This further confirms that the essence of human intelligence is the most complex grace of God's creation, as a control over artificial intelligence.